Evaluation of the accuracy of SRTM3 and ASTER GDEM in the Tibetan Plateau mountain ranges - Jin, Yao; Yi, Chao-lu; Fu, Ping (EDP Sciences, 2020)
Topographic data on The Tibetan Plateau (TP) terrain are fundamental for geoscientific research, but are difficult to obtain. The Shuttle Radar Topographic Mission (SRTM) Digital Elevation Model (DEM) and the Advanced Spaceborne Thermal Emission and Reflection Radiometer Global Digital Elevation Model (ASTER GDEM) are two commonly used GDEM data. Verifying the accuracy of the two dataset for the TP mountain areas provides a reference point for the application of both DEMs. For evaluating the elevation accuracy and topographic information, we used 8242 field measurements from Differential Global Positioning System (DGPS) points and DEM data generated from 1:100,000 topographic maps to examine the accuracy of ASTER GDEM V2 and SRTM3 V4.1 elevation results. The average RMSE for elevation differences between DGPS and ASTER GDEM across the study areas was 18.56m while the average RMSE between DGPS and SRTM3 was 10.39m. The average RMSEs of ASTER GDEM and SRTM3 in glaciated areas were 8.55m and 5.87m, respectively. The vertical accuracy of SRTM3 is better than that of ASTER GDEM. The vertical accuracy of both DEMs do not vary with altitude, but is related to aspect and slope.